Structural Studies of Hantaan Virus - Battisti, Anthony J. (American Society for Microbiology (ASM), 2011)
Hantaan virus is the prototypic member of the Hantavirus genus within the family Bunyaviridae and is a causative agent of the potentially fatal hemorrhagic fever with renal syndrome. The Bunyaviridae are a family of negative-sense RNA viruses with three-part segmented genomes. Virions are enveloped and decorated with spikes derived from a pair of glycoproteins (Gn and Gc). Here, we present cryo-electron tomography and single-particle cryo-electron microscopy studies of Hantaan virus virions. We have determined the structure of the tetrameric Gn-Gc spike complex to a resolution of 2.5 nm and show that spikes are ordered in lattices on the virion surface. Large cytoplasmic extensions associated with each Gn-Gc spike also form a lattice on the inner surface of the viral membrane. Rod-shaped ribonucleoprotein complexes are arranged into nearly parallel pairs and triplets within virions. Our results differ from the T=12 icosahedral organization found for some bunyaviruses. However, a comparison of our results with the previous tomographic studies of the nonpathogenic Tula hantavirus indicates a common structural organization for hantaviruses.